2005
DOI: 10.1111/j.1479-828x.2005.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

How useful are hospital morbidity data for monitoring conditions occurring in the perinatal period?

Abstract: While hospital administrative data are readily available, data quality is a valid concern. However, if the data are viewed critically and information on accuracy is available, they can be a useful resource for monitoring the health of mothers and babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
125
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 10 publications
10
125
0
Order By: Relevance
“…A validation study comparing data in the APDC to medical records found neonatal jaundice had a sensitivity of 80.0% and a positive predictive value of 90.9%. 15 As a test of face validity, we found 87% of infants who had a diagnosis of jaundice received a procedure code for phototherapy, similar to the reported high positive predictive value. …”
supporting
confidence: 51%
“…A validation study comparing data in the APDC to medical records found neonatal jaundice had a sensitivity of 80.0% and a positive predictive value of 90.9%. 15 As a test of face validity, we found 87% of infants who had a diagnosis of jaundice received a procedure code for phototherapy, similar to the reported high positive predictive value. …”
supporting
confidence: 51%
“…24,25 This study showed that combining smoking information from the birth and hospital admission data enhanced the identification of pregnant smokers and improved the estimates of prevalence of smoking during pregnancy among Australian women. Estimates of the effects of maternal smoking on placental abruption, preterm birth, stillbirth and low birthweight were similar to those in the published literature, irrespective of whether unenhanced or enhanced methods were used.…”
Section: Discussionmentioning
confidence: 89%
“…37 Although no separate data source was available to compare the enhanced identification of smokers, by benchmarking findings against the population-based surveys this research has demonstrated that the enhanced algorithms produce estimates of maternal smoking prevalence that are similar to the expected rates of smoking in women of reproductive age. Low false positives for smoking in birth records and hospital records 24,25,54 suggest that the use of linked data reduced the number of smokers who were incorrectly reported as nonsmokers, rather than incorrectly identifying non-smokers as smokers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations